ISSUES IN THE NOBLE HADITH (Islamic Sciences Journal, 2023)
Praise be to God, whose righteous grace is fulfilled and enlightened with the darker opening of the closed seals. It was clear from what has been discussed with us from several matters that we summarize the most important of them: -1- The cause in the hadith is divided into a phenomenon which is hidden and what the scholars want from studying the cause is the invisible cause, as it was formed by many people of workmanship that is harmful to the authenticity of the hadith.2- The scholars differed regarding the concept of the cause of it on several sayings, until some of them counted each leading to the authenticity of the hadith.3- That knowledge of the cause in one of the most honorable hadith sciences is one of the ways for scholars to come to the revision of the hadith and to explain its authenticity from its narration.4- The science of the ailments is one of the most difficult sciences, so that it is hardly escaped by the weakened of its importance and the scarcity of its goods in modern science.5-That the science of ills is a renewed science that God Almighty may open to someone who has seen what is hidden from others, to place another officer not mentioned by other scholars.